Reconstructing Prosecutorial Epistemology for Substantive Justice in Contract Law: A Comparative Philosophical and International Legal Analysis of Indonesia and Kazakhstan - Yuvita Tri Mardiana; Fendi Setyawan; Muhammad Arief Amrullah; Ayu Herlin Norma Yunita; Dametken Medikhanovna Turekulova (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: Contemporary contract law in Indonesia and Kazakhstan faces persistent tension between private autonomy and substantive justice. Both jurisdictions enshrine the principle of good faith, yet lack clear doctrinal guidance for its application, resulting in inconsistencies in interpretation and enforcement within their respective civil law systems. Purposes of the Research: This study aims to examine how prosecutors within these jurisdictions construct legal knowledge and exercise discretion when intervening in contract-related disputes, and to evaluate whether such prosecutorial practices advance or hinder the realization of substantive justice in contractual enforcement. Methods of the Research: This research employs a normative–juridical method complemented by comparative and philosophical approaches. It analyses statutory provisions, judicial reasoning, and international soft-law instruments—particularly the UNIDROIT Principles of International Commercial Contracts—to explore how discretion and evidentiary reasoning shape enforcement. Results Main Findings of the Research: The findings reveal that Indonesian prosecutors, inheriting a Roman-Dutch legacy, invoke good faith inconsistently due to evidentiary ambiguity and weak pre-contractual standards, while Kazakh prosecutors emphasize formal legality that sidelines moral reasoning. This research contributes to comparative legal philosophy by proposing three reconstructive pillars for prosecutorial reasoning—doctrinal clarity, evidentiary proportionality, and principled discretion—to align substantive justice with fairness-oriented norms.